Peningkatan Hasil Belajar Siswa MTs Ma’arif Kedungkendo dengan Komik Tata Surya - Lestari, Eka; Shofiyah, Noly (Inquest Journal, 2024)
This study investigates the impact of solar system comic-book media on the learning outcomes of seventh-grade students. Utilizing a quantitative pre-test and post-test experimental design, the research involved control and experimental classes. The instruments comprised a 20-question multiple-choice pre-test and post-test, with the results analyzed using the independent t-test and significance level < 0.05. The findings reveal a significant improvement in students' learning outcomes post-treatment, indicating the effectiveness of comic-book media in enhancing science education. This study underscores the potential of integrating comic-book media into the curriculum to boost student engagement and understanding